Norcantharidin down-regulates iron contents in the liver and spleen of lipopolysaccharide-treated mice - Jie Zheng; Jiao-Jiao Wang; Hui-Min Ma; Meng-Qi Shen; Zhong-Ming Qian; Yu-Xin Bao (Taylor & Francis Group, 2022)
Objective The inhibiting effect of Norcantharidin (NCTD) on IL-6 (interleukin-6) and STAT3 and the involvement of the IL-6/STAT3 pathway in hepcidin expression prompted us to speculate that NCTD could affect iron metabolism.Methods We examined the effects of NCTD on serum iron (SI) and transferrin (Tf) saturation, iron and ferritin light chain (FTL), transferrin receptor 1 (TfR1), divalent metal transporter 1 (DMT1), ferroportin 1 (Fpn1), iron regulatory protein 1 (IRP1) and hepcidin, as well as IL-6 and STAT3 in the liver, spleen and duodenum of mice treated with lipopolysaccharide (LPS) in vivo, using RT-PCR, Western blotting and immunofluorescence analysis. Results NCTD could increase SI and Tf saturation and reduce tissue iron and FTL content by affecting expression of cell-iron transport proteins TfR1, DMT1 and Fpn1. The impact of NCTD on TfR1, DMT1 and Fpn1 expression is mediated by up-regulating IRP1 and down-regulating hepcidin expression, while NCTD-induced down-regulation of hepcidin is mediated by the IL-6/STAT3 signalling pathway in LPS-treated mice. Conclusions NCTD affects iron metabolism by modifying the expression of IL-6/JAK2/STAT3/hepcidin and IRP1 and suggest that the ability of NCTD to reduce tissue iron contents may be a novel mechanism associated with the anti-cancer effects of NCTD.